2000
DOI: 10.1021/es990959q
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2,3,7,8 Specific Congener and Toxic Potency of Persistent Polychlorinated Dibenzo-p-Dioxins and Polychlorinated Dibenzofurans in Cetaceans from the Mediterranean Sea, Italy

Abstract: The present study investigates individual 2,3,7,8-substituted polychlorinated dibenzo-p-dioxin (PCDD) and polychlorinated dibenzofuran (PCDF) concentrations in cetaceans and assesses the PCDD and PCDF contributions to the total TCDD equivalent concentration. Liver samples of a variety of cetaceans species found stranded along the Italian coasts during the period of 1987−1992 were analyzed for PCDDs and PCDFs. The main aims were to scrutinize levels and patterns of PCDDs and PCDFs for the first time in cetacean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 52 publications
3
5
2
Order By: Relevance
“…Previous studies have shown that the OC concentrations determined by the HPLC/PDA method are in good agreement with the values measured by other, more frequently used analytical methods (e.g., gas chromatography/ electron-capture detection and gas chromatography/mass spectrometry) for a wide range of marine biota matrices, including marine mammal blubber [26,27]. Previous contaminant studies have shown that dioxin-like PCBs are greater contributors (usually Ͼ80%) to the total TEQs compared to the PCDDs and PCDFs in marine mammals [29][30][31][32]. The OCs were separated from interfering compounds (e.g., lipids and aromatic compounds) in the sample extracts by elution with hexane/methylene chloride (1:1, v/v) on a gravity-flow cleanup column that contained neutral, basic, and acidic silica gels.…”
Section: Organochlorine and Lipid Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies have shown that the OC concentrations determined by the HPLC/PDA method are in good agreement with the values measured by other, more frequently used analytical methods (e.g., gas chromatography/ electron-capture detection and gas chromatography/mass spectrometry) for a wide range of marine biota matrices, including marine mammal blubber [26,27]. Previous contaminant studies have shown that dioxin-like PCBs are greater contributors (usually Ͼ80%) to the total TEQs compared to the PCDDs and PCDFs in marine mammals [29][30][31][32]. The OCs were separated from interfering compounds (e.g., lipids and aromatic compounds) in the sample extracts by elution with hexane/methylene chloride (1:1, v/v) on a gravity-flow cleanup column that contained neutral, basic, and acidic silica gels.…”
Section: Organochlorine and Lipid Analysissupporting
confidence: 80%
“…Although the TEQs determined in the sea lion blubber samples were conservative values, both because they did not include polychlorinated dibenzodioxins (PCDDs) or polychlorinated dibenzofurans (PCDFs) and because the limit of detection for dioxin-like PCBs for the HPLC/ PDA method were higher than those measured by high-resolution gas chromatography/mass spectrometry, they provide an estimate of toxic potency in the samples. Previous contaminant studies have shown that dioxin-like PCBs are greater contributors (usually Ͼ80%) to the total TEQs compared to the PCDDs and PCDFs in marine mammals [29][30][31][32]. For example, Ross et al [33] found that dioxin-like PCBs contributed more than 90% to the total TEQs determined in blubber of harbor seal pups from Puget Sound (WA, USA).…”
Section: Organochlorine and Lipid Analysismentioning
confidence: 99%
“…Because dietary uptake is the major route of dioxin exposure in humans, numerous studies have been conducted to determine the occurrence of dioxin in fish and other aquatic organisms from freshwater and marine environments (1,5,7). Recently, many studies have focused on high trophic level animals such as seabirds, cetaceans, and seals, using them as bioindicators for monitoring marine pollution (6,(8)(9)(10)(11)(12). In addition to the studies on the accumulation of dioxin in high trophic level animals, biomagnification in the food web has also been described (4,13) by using stable isotopes of nitrogen to provide continuous trophic levels, a method which has been used to study the dynamics of polychlorinated biphenyls (PCBs) and organochlorine contaminants in marine and freshwater food webs (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental monitoring of 2,3,7,8-tetrachloro-dibenzo-para-dioxin (2,3,7,8-TCDD) is extremely relevant due to its high toxicity to man. 2,3,7,8-TCDD is the most toxic isomer among all the polychlorinated dibenzo-para-dioxins and its sole determination is sufficient to establish pollution risk . Gas-chromatography mass spectrometry (GC/MS) and high-performance liquid chromatography (HPLC) are only capable of determining the total “dioxin” fraction.…”
mentioning
confidence: 99%